PELAYANAN SISTEM IDUHELP (ILEARNING EDUCATION HELP) DENGAN MENGGUNAKAN SISTEM ILEARNING SURVEY PADA PERGURUAN TINGGI - Hani Dewi Ariessanti; Erick Febriyanto; Nida Hanifah (CCIT Journal, 2014)
Service is an activity undertaken by individuals or groups of people through the system, certain procedures and methods in order to meet the needs of others with the easiness to meet all their needs. From the development of informatics technology in today’s world, then by using a system called iDuHelp !, Allows students to get information about ilearning. With this system, students can enjoy the services of two services , namely online and offline. implementation of student satisfaction on a given service activity to satisfaction with the service system creates realistic, so of service iDuHelp ! provide a system that is shaped survey ilearning survey . The system can be filled by students in the form of a link, contains questions on pelyanan iDuHelp !. Thus the survey iLearning system contribute maximize quality improvement and provide good service and to improve the overall performance of the operator in providing services to customers. Many related methods of this study, such as by using the method ilearning. So that a clear research using mind mapping. In this study explained about the problems encountered and solutions are included in the form of a flowchart. the implementation of the system are protptype iDuHelp ! and iLearning Survey .Results in the form of a graph of Isur customer response to operator services and systems, so it is useful to improve the overall service quality iDuHelp! system.